THE USE OF THE TEMPERATURE CRITERIA FOR OPTIMIZING THE GEOMETRY OF DEFORMING ZONES AND CALIBRATING CHANNEL WIRE - A. V. Vedeneev; Yu. L. Bobarikin; M. N. Vereshchagin; M. A. Zeluev (Литьë и металлургия)
The methods of optimization of the die channel geometry at wire drawing by the temperature criterion enabling to project geometry of deforming and calibrating zones of die are created.